Use of the Second Dorsal Metacarpal Artery-Based Bilobed Island Flap for Thumb Reconstruction - Zhang, Xu; Shao, Xinzhong; Ren, Chunzhen; Wen, Sumin; Zhu, Hongwei; Sun, Jianxin (Journal of Reconstructive Microsurgery, 2012)
We report the use of the second dorsal metacarpal artery-based bilobed island flap harvested from the index and middle fingers for thumb reconstruction. From October 2006 to March 2008, the flap was performed in 13 hands in 13 patients (10 males and 3 females). The mean age at the time of operation was 45 years (range, 38 to 57 years). The flaps of the index fingers ranged in size from 2.1 × 2.5 cm to 4.2 × 3.2 cm. The flaps of the middle fingers were from 2.5 × 2.5 cm to 4.7 × 3.0 cm. The mean pedicle length was 6.5 cm (range, 5.1 to 8.0 cm). Flap survival was achieved in all cases. At final follow-up (mean 43 months; range, 36 to 52 months), the mean static two-point discrimination of the thumb pulps was 7 mm (range, 5 to 10 mm). Our technique is useful and reliable for the thumb reconstruction in select cases, with minimal donor-site morbidity.
Keywords: second dorsal metacarpal artery-based bilobed island flap; second dorsal metacarpal artery; thumb reconstruction